2010
DOI: 10.1007/s11192-010-0265-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between impact and collaboration

Abstract: We obtained data of statistical significance to verify the intuitive impression that collaboration leads to higher impact. We selected eight scientific journals to analyze the correlations between the number of citations and the number of coauthors. For different journals, the single-authored articles always contained the lowest citations. The citations to those articles with fewer than five coauthors are lower than the average citations of the journal. We also provided a simple measurement to the value of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 7 publications
3
39
1
1
Order By: Relevance
“…There is evidence that work performed in collaboration receives more citations (Lewinson and Cunningham 1991;Narin et al 1991;Katz and Hicks 1997;Glänzel 2001Glänzel , 2002Aksnes 2003;Persson et al 2004;Leimu and Koricheva 2005;Moya-Anegón et al 2008;Chinchilla-Rodríguez et al 2010;Hsu and Huang 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that work performed in collaboration receives more citations (Lewinson and Cunningham 1991;Narin et al 1991;Katz and Hicks 1997;Glänzel 2001Glänzel , 2002Aksnes 2003;Persson et al 2004;Leimu and Koricheva 2005;Moya-Anegón et al 2008;Chinchilla-Rodríguez et al 2010;Hsu and Huang 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific projects are increasingly complex, and these projects demand skills from many areas (Abt, 2007b;Nabout et al, 2015). Articles with more than four authors, for instance, have more citations and, consequently, involve several institutions from different areas (Leimu and Koricheva, 2005;Hsu and Huang, 2011). In addition, it is commonly understood that the most important metric in measuring article quality is the number of times it is cited, independent of other quantitative attributes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the effect of language of publication on CPP was analyzed. Some research has demonstrated a positive effect of the number of authors, affiliations, or countries participating on a paper on its ‘citedness’ [27],[39]–[41]. In light of this, it is possible that domestic papers might be less cited than bilateral papers, and bilateral papers less cited than multilateral or international collaborations.…”
Section: Methodsmentioning
confidence: 99%